2021
DOI: 10.3354/meps13825
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variability in the deposition of beach-cast kelp (wrack) and inter-specific differences in degradation rates

Abstract: Coastal habitats dominated by marine macroalgae typically exhibit high rates of primary productivity and play a key role in local and regional carbon cycles and stores. In temperate regions, large brown algae (i.e. kelps and fucoids) contribute significantly to macroalgal primary production, most of which is exported from source habitats as detritus. The ultimate fate of this detritus and the processes controlling detrital pathways into food webs and carbon cycles remain poorly understood. Based on field surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 79 publications
2
2
0
Order By: Relevance
“…This estimate is likely to be broadly representative of L. hyperborea populations across its range in the NE Atlantic, as our northern populations are similar in structure to those in Norway and our southernmost populations akin to those in France and Spain (Jupp and Drew 1974; Pedersen et al 2012; Pessarrodona et al 2018). These findings support the emerging role of L. hyperborea forests as key donors of organic matter to a range of recipient habitats in the NE Atlantic (Smale et al 2018; Ramirez‐Llodra et al 2021; Gilson et al 2021 a ), and advance our understanding of rates of detrital release, export, and persistence along dynamic wave‐exposed coastlines dominated by extensive kelp forests.…”
Section: Discussionsupporting
confidence: 73%
“…This estimate is likely to be broadly representative of L. hyperborea populations across its range in the NE Atlantic, as our northern populations are similar in structure to those in Norway and our southernmost populations akin to those in France and Spain (Jupp and Drew 1974; Pedersen et al 2012; Pessarrodona et al 2018). These findings support the emerging role of L. hyperborea forests as key donors of organic matter to a range of recipient habitats in the NE Atlantic (Smale et al 2018; Ramirez‐Llodra et al 2021; Gilson et al 2021 a ), and advance our understanding of rates of detrital release, export, and persistence along dynamic wave‐exposed coastlines dominated by extensive kelp forests.…”
Section: Discussionsupporting
confidence: 73%
“…In general, wave energy dissipation rates are higher over immobile, rough bed forms than over mobile sandy lake beds or mudflats [115]. In line with this Gilson et al [97] found a generally lower wrack biomass on sandy sites than on pebble shores of marine tidal coasts in NW Ireland.…”
Section: Sediment Texturementioning
confidence: 87%
“…The abundance of wrack can be quantified by visual estimation of cover percentage [ 39 , 96 , 97 ], by measuring its width and height [ 31 ], by calculating its volume [ 40 ], or by taking representative samples and calculating the wet weight, dry weight or ash-free dry weight [ 32 , 35 , 40 , 98 ]. We used the wrack width and height to capture variability across sites in an efficient way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of kelp‐derived production (>80%) enters the food web through detrital pathways, with high rates of export from source populations and the potential for long‐distance transport to recipient ecosystems (Krumhansl & Scheibling, 2012 ). This transfer of carbon has been shown to constitute a crucial trophic subsidy in a range of habitats, including rocky shores, sandy beaches, submarine canyons, and the deep‐sea (Gilson, Smale, Burrows, et al, 2021 ; Krumhansl & Scheibling, 2012 ; Polis et al, 1997 ). Detrital production is generated by two primary mechanisms, chronic erosion of material (typically from the distal part of the blade) or dislodgment of sections or entire thalli (de Bettignies et al, 2013 ; Krumhansl & Scheibling, 2011 ).…”
Section: Introductionmentioning
confidence: 99%